International Project in Higher Education: Influence of Chinese Culture - BEKAREVA, Svetlana V.; MELTENISOVA, Ekaterina N.; XUEQING, Zu (Journal of Research in Educational Sciences; Vol 9 No 11 (2018): JRES Volume IX Number 11_2018, 2019)
Development of universities striving to be successful on the international scene is closely connected with internationalization of higher education, which, in turn, requires taking into account the features of interacting cultures in the process of educating students on the one hand and high qualifications of the faculty on the other. The article describes the experience of Novosibirsk State University (NSU, Novosibirsk, Russia) and Heilongjiang University (Harbin, China) in organizing an international project in the field of higher education. We launched an academic program International Finance, which has proved a successful international project. We share our experience how theories of Intercultural Communication (ICC) and practical skills in the area can be used in promoting such projects.